A Comparison of Percutaneous Ablation Therapy to Partial Nephrectomy for cT1a Renal Cancers: Results from the Canadian Kidney Cancer Information System. Issue 4 (10th October 2022) - Millan, Braden; Breau, Rodney H.; Bhindi, Bimal; Mallick, Ranjeeta; Tanguay, Simon; Finelli, Antonio; Lavallée, Luke T.; Pouliot, Frédéric; Rendon, Ricardo; So, Alan I.; Dean, Lucas; Lattouf, Jean-Baptiste; et al.
Abstract : Purpose: Percutaneous ablation therapy (AT) and partial nephrectomy (PN) are successful management strategies for T1a renal cancer. Our objective was to compare AT to PN with respect to recurrence-free survival (RFS) and overall survival (OS). Materials and Methods: Patients post-PN or -AT for cT1aN0M0 renal cancer from 2011 to 2021 were identified from the national Canadian Kidney Cancer information system. Inverse probability of treatment weighting (IPTW) using propensity score (PS) was used. The primary outcomes, RFS and OS, were compared using Kaplan-Meier log-rank test analyses and Cox proportional hazard regression models. Results: A total of 275 patients underwent AT and 2, 001 underwent PN, with a median followup of 2.0 years (IQR 0.6–4.1). Covariates were well balanced between the AT and PN cohorts following PS matching. Two-year RFS following IPTW PS analysis for patients undergoing AT and PN was 88.1% and 97.4% (p <0.0001), respectively, while 2-year OS was 97.4% and 99.0% (p=0.7), respectively. Five-year RFS following IPTW PS analysis for patients undergoing AT and PN was 86.0% and 95.1%, respectively (p=0.003), while 5-year OS was 94.2% and 95.1%, respectively (p=0.9). Following IPTW PS analysis, treatment modality (PN vs AT) was a predictor of disease recurrence (HR 0.36, p=0.003) but not for OS (HR 0.96, p=0.9). Conclusions: With short followup, PN offers better RFS than AT, although no significant difference in OS was detected following PS adjustments. Both modalities can be offered to appropriately selected patients while we await prospective randomized data.